Modern Approach to Teaching Pedagogical Skills of Teachers - Gulnora Jumayeva (International Journal on Integrated Education, 2021)
The article analyzes the specifics of the modern approach to improving the pedagogical experience of teachers as a source of pedagogical creativity in the modern era of science and technology. The article also analyzes the classification of theories on the management of creative pedagogical activity and the development of pedagogical skills of teachers.